2021
DOI: 10.3390/agronomy11040792
|View full text |Cite
|
Sign up to set email alerts
|

A New Identification Method Reveals the Resistance of an Extensive-Source Radish Collection to Plasmodiophora brassicae Race 4

Abstract: Raphanus sativus, an important cruciferous vegetable, has been increasingly affected by clubroot disease. Establishing a stable and accurate resistance identification method for screening resistant germplasms is urgently needed in radish. In this study, the influence of inoculum concentration, inoculation methods, and pH of the substrate on disease occurrence was studied. The result showed that the disease index (DI) was highest at 2 × 108 spores/mL, the efficiency of two-stage combined inoculation methods was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…A recent study reported that the majority of the tested radish germplasm was susceptible to the clubroot pathogen, including 81 susceptible and 204 highly susceptible accessions based on the DIs of an extensive source collection of 349 accessions. Exotic radish germplasm has a higher degree of resistance to clubroot disease than local Chinese radish cultivars [29]. However, early studies indicated that the majority of radish cultivars and inbred lines possess a high degree of resistance [32,40], which may reflect differences in the tested germplasm and pathogen races.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study reported that the majority of the tested radish germplasm was susceptible to the clubroot pathogen, including 81 susceptible and 204 highly susceptible accessions based on the DIs of an extensive source collection of 349 accessions. Exotic radish germplasm has a higher degree of resistance to clubroot disease than local Chinese radish cultivars [29]. However, early studies indicated that the majority of radish cultivars and inbred lines possess a high degree of resistance [32,40], which may reflect differences in the tested germplasm and pathogen races.…”
Section: Discussionmentioning
confidence: 99%
“…Radish develops an enlarged taproot with few fibrous roots, which may result in infection symptoms that are initially inconspicuous and only subsequently become visible. Precise and reliable artificial inoculation of radish with P. brassicae is not straightforward compared with inoculation of other cruciferous crops [1,29]. Yang et al evaluated the clubroot resistance of a radish germplasm collection using a two-stage inoculation method combining bud injection and injury to the seedling root, which achieved superior stability and accuracy of infection compared to a single-inoculation method [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pathotypes highlight the ability of P. brassicae to diversify and adapt to given conditions [ 17 , 18 ]. Due to genetic variability, numerous isolates of P. brassicae with different pathogenicity can be found worldwide [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%